Electrochemical Synthesis of 2-Bromoethyl and 2-Iodoethyl Ketones from Cyclopropanols - Barysevich, Maryia V.; Aniskevich, Yauhen M.; Hurski, Alaksiej L. (Synlett, 2021)
A simple electrochemical protocol for the preparation of 2-bromoethyl- and 2-iodoethyl ketones from cyclopropanols and magnesium halides has been developed. The reaction proceeded with exclusive regioselectivity and without epimerization of the α-stereocenter in the products. We also showed that the synthesized diastereomerically pure 2-bromoethyl ketones undergo smooth copper and nickel-catalyzed alkylation, alkenylation, and arylations reactions.
Keywords: electrochemistry; cyclopropanols; haloethyl ketones; ring opening; cross-coupling